Efeitos da testosterona sobre a reatividade vascular de ratos hipertensos - Gonçalves, Leticia Tinoco (2023)
The abusive use of testosterone is considered a global public health problem, with several side effects. In the cardiovascular system, its effects are still controversial, ranging from protective to deleterious actions. Because testosterone is a hormone that can be converted to 17 β-estradiol and dihydrotestosterone (DHT), part of the effects found with supraphysiological doses can be attributed to its metabolites. Therefore, we investigated the hypothesis that a supraphysiological dose of testosterone impairs the endothelium-dependent vasodilation of mesenteric resistance arteries, as well as its repercussions on oxidative stress (OS) and blood pressure (BP). We also evaluated the participation of 17 β-estradiol and DHT in the responses found. We used Spontaneously Hypertensive Rats (SHR), aged 8 to 10 weeks, divided into 5 groups: intact (SHAM), orchiectomized (ORX), intact testosterone-treated (TTO; 3 mg/Kg/day/s.c.), intact treated with testosterone and anastrozole [aromatase enzyme inhibitor (TTO+ANA; 0.1 mg/Kg/day)] and intact treated with testosterone and finasteride [5α-reductase enzyme inhibitor (TTO+FIN; 5 mg/Kg/day)] for 4 weeks. BP was assessed by tail cuff plethysmography. We performed concentration-response curves to acetylcholine (ACh, 0.1 nM - 10 µM) in mesenteric arteries using a wire myograph, in the absence and presence of pharmacological inhibitors. Also testosterone, 17 β-estradiol and dihydrotestosterone concentrations were evaluated. Vascular detection of superoxide anion (O2 •- ) and endothelium ultrastructure were analyzed by DHE and scanning electron microscopy (SEM), respectively. Data were expressed as mean ± standard error of the mean, and analyzed by Student's t-test or one-way or two-way ANOVA, followed by Tukey's post hoc test (p < 0.05). Orchiectomy reduced levels of testosterone, 17 β-estradiol and dihydrotestosterone, impaired ACh vasodilation, increased OS, altered endothelial morphology without altering BP. Testosterone treatment did not impair ACh vasodilation compared to the SHAM group, however it altered the endothelial pathways of relaxation, with lesser participation of NO and greater participation of prostanoids, possibly derived from COX-1. In addition, in the TTO group, the participation of EDH was greater compared to SHAM, indicating that EETs, H2O2 and K+ channels contributed to this vasodilator response. In the TTO+ANA group, the reduction in 17 β-estradiol levels did not impair ACh vasodilation, however, it decreased the participation of nitric oxide, prostanoids and increased EDH, and increased O2•- levels with alteration of endothelial morphology. TTO+FIN showed impairment in the vasodilator response to ACh, with an increased participation of NO and a lower participation of prostanoids. Regarding EDH, with a decrease in dihydrotestosterone, there was no increase in the participation of EETs, H2O2 and K+ channels compared to TTO. DHT seems to contribute to the decrease of NO and estrogen seems to stimulate the action of the NO pathway and prostanoids. In estrogen reduction, testosterone maintains endothelial vasodilation by greater stimulation of EDH, with more action of EETs, H2O2 and K+ channels, with greater formation of O2 •- . These results may contribute to the elucidation of the modulating role of testosterone on endothelial function, even in treatment with a supraphysiological dose, in addition to showing the importance of the presence of estrogen for the cardiovascular system in situations of endothelial dysfunction.